A STUDY ON STRATEGIES USED IN DEVELOPING SPEAKING SKILLS - Adrian; Kamaruddin , Abdul; Aminah, Aminah; Dewi, Anjar Kusuma (e-Journal of ELTS (English Language Teaching Society), 2023)
The objective of this study is to examine and analyze articles concerning the strategies used in developing speaking skills published in between 2018 to 2023. This research employs library research methodology, which involves using library sources to gather and analyze data. The research results shows that the strategies used in developing speaking skills are Communication Strategies, Task-Based Approaches, Role-Play, and Technology-Enhanced Approaches and the most frequently used strategies are Role-Play, and Technology-Enhanced Approaches. To implement the two most frequent strategies used, educators need a careful planning and consideration. They should introduce concepts, select relevant content, and provide clear instructions. Technology can enhance authenticity and engagement in speaking activities by utilizing tools like YouTube, digital storytelling, or educational comics. In conclusion, this research provides valuable insights into the strategies employed to develop speaking skills.